GULBADAN BEGUM : KONTRIBUSINYA DALAM KESULTANAN MUGHAL (929-1011 H/1523-1603 M) - Muhammad Abdullah; Sri Suriana (Program Studi Sejarah Peradaban Islam UIN Raden Fatah Palembang, 1970)
This study aims to analyze and see how Gulbadan Begum's contribution to the Mughal Sultanate. This research is a qualitative research and uses a historical methodology through library research based on a comparison of the data obtained and processed by the author, and describes what Gulbadan Begum did during the reign of Sultan Humayun and Sultan Akbar, and contributions to science. knowledge. The results of this study resulted in some of the best policies for the palace of the Mughal Sultanate. In addition, several scientists appeared in the Mughal Sultanate who made when Sultan Akbar ruled it was written that his era was the era of the pride of the Mughal Sultanate